Wacana Sistem Kepercayaan Masyarakat Waropen Dalam Narasi Munaba (Analisis Antropologi Sastra) - Be Yenusi, Belghita Sonei Risia (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 23 (2016): March 2016, 2016)
This study focused on discourse of the tribal religion in narrative poetry munaba from Waropen ethnic, Papua. Munaba was selected due to its familiar and grounded in local communities in the area. Research approach is based on text and context. The approach focused on literary works and based on some aspects such as history, culture, and religion. The study used descriptive qualitative method which uncovered facts, phenomenon and variable. The study as well interpreted data related to given situation, the view points of society, conflicts, the difference between facts, and the influence of particular problem which was studied and investigated. The data was obtained from oral literature which was shared by the native speakers. In addition, the research also applied observation. Data source is munaba in Waropen language. The original data has been transliterated from a number of informants then it’s translated into bahasa. Based on the discourse theory and anthropology literature analysis, the study found some forms tribal religion such as the believing in God, believing in the spririt of ancestor, and believing in magic power.
Keywords: discourse, tribal religion, munaba, Waropen